PENINGKATAN PEMAHAMAN KONSEP PEMBAGIAN PECAHAN DENGAN PENDEKATAN REALISTIC MATHEMATIC EDUCATION DI KELAS V SDN 003 PULAU KOPUNG KECAMTAN SENTAJO RAYA KABUPATEN KUANTAN SINGINGI - Sri Apnita Indra (JURNAL PAJAR (Pendidikan dan Pengajaran), 2019)
Mathematics lessons, especially fractions, need to be given to all students starting from elementary school to equip students with the ability to think logically, analytically and creatively, and the ability to cooperate. Fractional material, in mathematics learning is difficult to learn by students in class V Elementary School 003 Kopung Island Sentajo. Fractions have been taught from low classes with introducing stages, fractions are equal, add up, subtract, multiply and divide various forms of fractions. However, student learning outcomes are still low. To improve the results of students' learning comprehension the researchers used the Realistic Mathematic Education (RME) approach. From the analysis of data on students' learning outcomes before and after the application of the Realistic Mathematic Education approach, only 10 students completed or 43.47% with incomplete categories. After the first cycle, students who completed it increased to 16 people or by 69.56% with incomplete categories. For the second cycle, the number of students who completed as many as 20 people or equal to 89.95% with complete categories.